(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Argumentation is a language of science that promotes critical thinking and reasoning skills. While it is a vital form of discourse used within the scientific community, it is also essential in preparing students to interact with science in their daily lives. Incorporating argumentation skills into the science classroom holds a usefulness in preparing students to be able to engage in socio-scientific issues they will face and in promoting scientific literacy. Science educators becoming aware of the importance of including argumentation will benefit students by encouraging critical thinking, reasoning, and communication. It will give students the skills necessary to be able to engage in discussions about issues faced in their lives and back their discussion with evidence.